Global bioethics - Neuhaus, Carolyn P. (The Hastings Center report, 2017)
This August, I participated in the conference “Genome Editing: Biomedical and Ethical Perspectives,” hosted by the Center for the Study of Bioethics at the University of Belgrade and cosponsored by the Division of Medical Ethics of NYU Langone Health and The Hastings Center. The prime minister of Serbia, Ana Brnabić, spoke of the significance of bringing together an international community of bioethicists, acknowledging that ethical, social, and legal issues surrounding gene editing technologies transcend national boundaries. Europe's Oviedo Convention prohibits human germline gene editing, and UNESCO's Universal Declaration on the Human Genome and Human Rights says that germline editing “could be contrary to human dignity,” an assault on humanity itself. Whether one agrees or not, engaging with the idea forces us to think about what it means to be part of the global human community and about the moral significance of the human genome to creating that community. The conference highlighted for me how challenging having international, much less global, conversations about bioethics can be.